POTENTIAL LOSS PENERIMAAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN (BPHTB) SEBAGAI PAJAK DAERAH DI KABUPATEN SAMBAS (SETELAH PEMBERLAKUAN UNDANG-UNDANG NOMOR 28 TAHUN 2009 - B61111045, URAY WIRIYA SAPUTRA (Jurnal Ekonomi Daerah (JEDA), 2014)
ABSTRACT The purpose of applying this research is to find out the potential loss from the revenue for Bea Perolehan Hak Atas Tanah dan Bangunan (BPHTB) as a local tax, the cause of the potential loss and to discover the effort that has been done by the government in Sambas Regency in optimizing the BPHTB revenue as a local tax in Sambas Regency. The result of the research shows that the value of the potential loss of the revenue from BPHTB as a local tax in Sambas Regency in 2011 which reach the point of 70.39% and having a reduction to 51.09% in 2012. The potential loss of this BPHTB is caused by the dishonesty of the taxpayers, the lack of understanding of the self assessment system application of the taxpayers in BPHTB payment, which enable the tendency of dishonesty from the taxpayers. For the government (in this case is Dinas Pendapatan Daerah Kabupaten Sambas) the lack of compatible human resources in supporting the management of BPHTB, inter-agency cooperation in managing the BPHTB such as notary, PPAT, BPN, KPP is not yet well-established, and the law enforcement which has not been fully implemented becomes another cause of the potential loss from the revenue of BPHTB as a local tax in Sambas Regency. From the result of SWOT analysis the effort of optimizing the revenue from BPHTB as a local tax in Sambas Regency is by using the strength-opportunities strategy (S-O) or aggressive strategy by using forces and authority, such as : 1. Implementing the local regulation forcefully, especially in conducting the supervision and evaluation regularly and continuously. 2. Gradually build, maintenance, and equip the infrastructure facility and supporting system of local revenue management. 3. Giving incentive and sufficient financial support in order to intensify the local revenue especially local tax revenue (BPHTB). 4. The inter-agency cooperation in managing the BPHTB such as notary, PPAT, BPN, KPP to formulate the policies in supervising the transaction value and improving the service for the taxpayers. 5. Improving the awareness of the taxpayers by implementing program and system appropriately. 6. Implementing the enforcement of the Law Number 28 Year 2009 by having initiative and creativity to the local's financial independency. 7. Encouraging the economic growth, increasing the quality and outcome of the local development, providing effective, efficient and maximum public services, creating safety, which will have implications and allowing a competitive circumstance to invest. Key word: BPHTB as a local tax, the dishonest taxpayers, potential loss.